ALIEN FISH SPECIES IN THE KARASHIK RIVER (SYRDARYA BASIN) (Experimental biology, 2023)
Alien species have become a widespread and influential factor in global environmental changes caused by humans. Water bodies of the Aral-Syrdarya basin are experiencing an increased anthropogenic load due to the withdrawal of large volumes of water for irrigation, and the unintentional introduction of a large number of alien fish species. The purpose of the study was to study the diversity of alien fish species in the Karashik river. This river is the only tributary from the Karatau mountains, which in high-water years can reach Syrdarya. Based on the analysis of stock materials collected in 2007-2017 and sampling from March to October 2022 and in June 2023, changes in the composition of alien fish species were established near the cities of Turkestan and Kentau. Most of the physico-chemical parameters of the water were at a level favorable for the life of all freshwater fish species. However, in many samples, an increased content of nitrates was noted, indicating anthropogenic pollution of this river. 6 species of alien fish with no commercial value were found: Abbotina Abbottina rivularis, rosy bitterling Rhodeus ocellatus, topmouth gudgeon Pseudorasbora parva, beautiful sleeper Hypseleotris cinctus, Chinese goby Rhinogobius cheni, Chinese rice-fish Oryzias sinensis. Of these, only the topmouth gudgeon was constantly found in the river, the diversity of other alien species varied over the years. Biological analysis has shown that habitat conditions allow the alien species to reproduce successfully, but prevent the achievement of bigger sizes,  known for water bodies with favorable habitat conditions.
Keywords: alien, fish, invasion, ecosystem, Syrdarya basin, indicator